A CRITICAL DISCOURSE ANALYSIS OF THE REPSERENTATION OF MISOGYNISTIC IDEOLOGY IN JOKO ANWAR’S HORROR FILMS 2017-2022 BASED ON RUTH WODAK’S APPROACH - Wa Ode Suci Rahmayani; Catur Nugroho (RADJA PUBLIKA, 2025)
This research examines the representation of misogynistic ideology in the horror films Pengabdi Setan (2017) and Pengabdi Setan 2: Communion (2022), directed by Joko Anwar, through Ruth Wodak’s Discourse-Historical Approach (DHA) within the framework of Critical Discourse Analysis (CDA). The study aims to analyze how misogynistic ideologies operate within the narratives of these two films and how they reproduce the patriarchal discourse embedded in Indonesian society. By investigating the male gaze, the research explores how this cinematic technique either reinforces or challenges misogynistic ideologies within the context of patriarchy. Furthermore, the study examines the role of symbolism and visual representation in these films, investigating how these elements are used to either create or resist the ideological framework of misogyny. Through a qualitative approach, CDA’s three key dimensions cognitive, socio-psychological, and linguistic are applied to reveal how gender power dynamics are conveyed through both narrative and visual forms in contemporary Indonesian horror cinema.